The Comparative Analysis of Affectâ€™s Realisation in The Tell-Tale Heart and The Black Cat Short Stories (Approach: Appraisal System) - Abd. Rahman Zain (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
Abstract. This study aims to investigate the realisation of affect in Edgar Allan Poeâ€™s short stories entitled The Tell-Tale Heart and The Black Cat. The short stories were analyzed using appraisal system adapted from Martin and White (2005). This study used qualitative method. The data are collected by using content analysis. The data were validated by 3 raters through Focus Group Discussion (FGD). The result shows that the most category of affect in The Tell-Tale Heart short story was â€œInsecurity: Disquietâ€ (33,33%). Meanwhile, in The Black Cat short story, the most category of affect was Unhappiness: Antiphaty (22,09%), Insecurity: Disquiet (18,60%), and Inclination: Desire (15,11%).Keywords: affect, appraisal, Edgar Allan Poe, short storiesAbstrak. Penelitian ini bertujuan untuk meneliti realisasi Affect pada cerita pendek Edgar Allan Poe yang berjudul The Tell-Tale Heart dan The Black Cat. Cerita pendek dianalisis menggunakan sistem Appraisal yang diadaptasi dari Martin dan White (2005). Penelitian ini menggunakan metode kualitatif. Data dikumpulkan menggunakan analisis isi. Data divalidasi oleh 3 penilai melalui Focus Group Discussion. Hasil penelitian menunjukkan bahwa kategori Affect terbanyak pada The Tell-Tale Heart adalah â€œInsecurity: Disquietâ€ (33,33%). Sementara pada The Black Cat kategori Affect terbanyak adalah Unhappiness: Antiphaty (22,09%), Insecurity: Disquiet (18,60%), dan Inclination: Desire (15,11%). Kata kunci: Affect, Appraisal, Edgar Allan Poe, cerita pendek